HUBUNGAN ANTARA PARAMETER ANTROPOMETRI DAN PROFIL LIPID PADA WANITA SEHAT DI SEMARANG - Rachma Purwanti; Ahmad Syauqy (PERSATUAN AHLI GIZI INDONESIA, 2022)
Obesity is associated with dyslipidemia and cardiovascular disease (CVD). The objective of the study was to determine the association between anthropometric parameters with lipid profiles among healthy women in Semarang. This study used a cross-sectional design with consecutive sampling. Anthropometric parameters in this research were body mass index (BMI), visceral fat, waist circumference (WC), hip circumference (HC), and waist-to-hip ratio (WHR). While, lipid profiles were total cholesterol, high-density lipoprotein (HDL), triglyceride (TG), low-density lipoprotein (LDL), and triglyceride and high-density lipoprotein ratio (TG/HDL). The association of anthropometric parameters with the lipid profiles was analyzed by Spearman correlation. Among subjects with nutritional status normal, BMI has significantly correlated with TG, HDL, and TG/HDL ratio. Moreover, WHR was significantly correlated with HDL and TG. While, among subjects overweight and obese, BMI, visceral fat, and WC were significantly correlated with TG, HDL, and TG/HDL ratio. Anthropometric parameters such as BMI, visceral fat, WC, and WHR were associated with lipid profiles among healthy women in Semarang. BMI and WHR can be used in individuals with normal nutritional status to predict lipid profiles. While, BMI, visceral fat, and WC can be used in overweight and obese individuals to predict lipid profiles